Research on stiffness and damping of the deep groove ball bearing under EHL conditions - XIA Boqian; DAI Yimin; ZHANG Zebin (Jixie chuandong)
ObjectiveOil lubricated rolling bearings can easily form elasto-hydrodynamic lubrication（EHL） between the rolling element and the raceway. The EHL oil film plays an important role in the stiffness and damping of rolling bearings, and the study and calculation of the stiffness and damping of rolling bearings must consider the role and influence of EHL oil film.MethodsApplying the fitting formula for stiffness and damping of point contact EHL friction pairs, the influence of load and speed on deep groove balls bearing stiffness and damping was investigated, and the theoretical calculation results were compared and analyzed with relevant test results.ResultsThe results show that the radial stiffness and damping of rolling bearings increase with the increase of load when the rotational speed is constant, and decrease exponentially with the increase of rotational speed when the load is constant. The variation trend of stiffness and damping of rolling bearings with load and speed is completely consistent with the test results, proving the correctness of the theoretical calculation results. The results also indicate that the fitting formula for stiffness and damping of point contact EHL friction pairs is correct, providing convenience for calculating the dynamic characteristics of rolling bearings under EHL conditions.